1989
DOI: 10.1111/j.1744-313x.1989.tb00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenetic Studies of Spontaneous Abortion in Mice: Iii. Non‐h‐2 Antigens and Gestation

Abstract: SUMMARY CBA/J (H‐2k) females, mated with DBA/2 J (H‐2d) or DBA/1 J (H‐2q) males, exhibit a high rate of fetal resorption. In contrast, when H‐2 identical CBA substrains (i.e. CBA/Ca and CBA/N) are used, this phenomenon is not observed. On the other hand, before mating with DBA/2 J males, pre‐immunization of CBA/J females with spleen cells coming from BALB/c J or (DBA/2 x BALB/c J) F1 males (and not from other H‐2d identical males whatever their Mls alleles) has significantly decreased the fetal resorption rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 15 publications
1
13
1
Order By: Relevance
“…Early studies suggested a high rate of non-pregnancy in DBA/2-mated CBA/J females (Clark, et al 1980). However, mothers of related CBA/J strains, CBA/Ca and CBA/N do not exhibit this phenomenon (Bobe and Kiger 1989). Investigators have noted that in DBA/2-mated CBA/J females, beginning around day 7 of gestation, there is a loss of cellular contact between decidual cells and cells of the ectoplacental cone (Gendron and Baines 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies suggested a high rate of non-pregnancy in DBA/2-mated CBA/J females (Clark, et al 1980). However, mothers of related CBA/J strains, CBA/Ca and CBA/N do not exhibit this phenomenon (Bobe and Kiger 1989). Investigators have noted that in DBA/2-mated CBA/J females, beginning around day 7 of gestation, there is a loss of cellular contact between decidual cells and cells of the ectoplacental cone (Gendron and Baines 1989).…”
Section: Introductionmentioning
confidence: 99%
“…As a high rate of embryonic loss in cloned pregnancies occurs concurrent with the initiation of intimate placental attachment, abnormalities in both placental development and fetomaternal interactions should be considered. Although maternal rejection of pregnancy is rare [23], it has been demonstrated in the mouse [24]. The possible role of the maternal response in causing pregnancy failure has been studied using interspecies pregnancies [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For many years, the most compelling animal model of immunologically mediated spontaneous fetal loss has been the murine (CBA/JϫDBA/2) mating combination, in which between 20 and 50% of the fetus is resorbed by gestational day 13 (15). The critical importance of this precise parental genetic combination and the ability to suppress fetal loss by preimmunizing females with BALB/c male lymphocytes or by prior mating to a BALB/c male (13,16) point to an immunological component that contributes to this fetal loss syndrome.…”
mentioning
confidence: 99%